UNCOVERING ACCOUNT FREEZING POLICIES: A BIBLIOMETRIC ANALYSIS OF DIGITAL TRANSACTION SECURITY AND FINANCIAL CRIME PREVENTION - Vyandri, Masadib Akmal; Maharani, Wydha Mustika (JPAP: Jurnal Penelitian Administrasi Publik, 2026)
The increasing use of digital financial services has raised concerns about transaction security and consumer protection, particularly in light of measures such as account freezes implemented by financial regulators, including the Financial Transaction Reports and Analysis Center (PPATK) in Indonesia. This study aims to analyze the impact of account freezes on digital transaction security and consumer rights, with a focus on the regulatory challenges and cross-border implications associated with such measures. A systematic review of the literature on fraud prevention, money laundering prevention, and consumer protection in digital finance was conducted. The findings indicate that while account freezes significantly reduce financial crime and improve transaction security, they also pose challenges, particularly for consumers whose accounts are unfairly frozen. Transparency, consumer literacy, and precise complaint mechanisms are crucial in mitigating these impacts. Furthermore, cross-border challenges in digital finance regulation complicate efforts to implement effective money laundering prevention measures globally, as data privacy laws and cryptocurrency regulations vary significantly across countries. This study contributes to understanding the balance between consumer security and accessibility in digital finance, highlighting the need for a coordinated regulatory framework. This study encourages further research into new technologies and global regulatory collaboration to address the challenges posed by account freezing in digital financial systems.